Tempeh Gembus Cookies as an Alternative Snack for Adolescent Girls With Obesity - Elserinawati Sinambela; Diana Nur Afifah; Hartanti Sandi Wijayanti; Fillah Fithra Dieny (Amerta Nutrition, 2020)
Background: Tempeh gembus is a food that high in protein and fiber but low in fat. The low content of fat in tempeh gembus is good for adolescent with obesity. Tempeh gembus cookies could be the alternative snack for adolescent girls with obesityObjectives: To analyze the effect of the substitution of tempeh gembus flour on the nutrient content of tempeh gembus cookies and the acceptability of the best formula on the tempeh gembus cookiesMethods: This was an experimental research with one factor complete randomized design, which was the formulation of cookies with tempeh gembus flour of 0%, 25%, 50%, and 100% as the variation of substitution, then analyzed the nutrients and acceptance. The statistic method used were One-way Anova test to analyze the nutrients and Friedman test to analyze the acceptanceResults: There were significant effects the formulation of cookies with tempeh gembus flour on total fat, carbohydrate, total crude fiber, ash content, and reducing sugar. In acceptance test, there were significant effects of tempeh gembus cookies formulation on color, appearance, tenderness, aroma, and flavorConclusions: Cookies with tempeh gembus flour formulation of 100% was the best formulation to meet total energy, carbohydrate, low fat and high fiber acceptance which were good for adolescent girls with obesity. Whereas cookies with tempeh gembus flour formulation of 25% and 50% based on acceptance were still acceptable and preferred